(untitled) (Bangladesh Journal of Public Administration, 2022)
Owing to the rapidly-growing economy and faster development of Bangladesh, the government has put weight on guaranteeing a non-intermittent and quality flow of electricity - to guarantee sustainable economic development. The State has made strategies for private sector participation and releasing marginal areas for energy production to diversify the electricity supply. To utilize these policies, the government designs large-scale renewable energy projects. Even though these projects are seen to be environmentally sound, they can hamper a community’s welfare if the result of the development is not reached the root level. Although solar energy is among the greenest forms of energy, not all societies can embrace it, as social, environmental and economic sustainability are the three factors that constitute total sustainability. This paper aims to qualitatively analyze the socio-economic prospects in the development of the large-scale solar park. It does a critical case study of a solar park of 10 megawatts (MW) capacity constructed on 40 acres of land in Tetulia of Panchagarh District. This structure began producing electricity in May 2019, which was added to the national grid. The research demonstrates how the advantages of renewable energy accumulate at the national and organizational level, and local communities face adverse effects. The paper recommends how social sustainability in such developments might be ensured in the future.